Quantum interferences reconstruction with low homodyne detection efficiency - Esposito, Martina; Randi, Francesco; Titimbo, Kelvin; Kourousias, Georgios; Curri, Alessio; Floreanini, Roberto; Parmigiani, Fulvio; Fausti, Daniele; Zimmermann, Klaus; Benatti, Fabio (EPJ Quantum Technology, 2016)
Optical homodyne tomography consists in reconstructing the quantum state of an optical field from repeated measurements of its amplitude at different field phases (homodyne data). The experimental noise, which unavoidably affects the homodyne data, leads to a detection efficiency η < 1. The problem of reconstructing quantum states from noisy homodyne data sets prompted an intense scientific debate about the presence or absence of a lower homodyne efficiency bound (η > 0.5) below which quantum features, like quantum interferences, cannot be retrieved. Here, by numerical experiments, we demonstrate that quantum interferences can be effectively reconstructed also for low homodyne detection efficiency. In particular, we address the challenging case of a Schrödinger cat state and test the minimax and adaptive Wigner function reconstruction technique by processing homodyne data distributed according to the chosen state but with an efficiency η < 0.5. By numerically reproducing the Schrödinger’s cat interference pattern, we give evidence that quantum state reconstruction is actually possible in these conditions, and provide a guideline for handling optical tomography based on homodyne data collected by low efficiency detectors.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Homodyne detection; Quantum tomography